Genetic analysis on growth and carcass traits in Nelore cattle - Zuin, R. G. [UNESP]; Buzanskas, M. E. [UNESP]; Caetano, S. L. [UNESP]; Venturini, G. C. [UNESP]; Guidolin, D. G. F. [UNESP]; Grossi, D. A. [UNESP]; Chud, T. C. S. [UNESP]; Paz, C. C. P.; Lobo, R. B.; Munari, D. P. [UNESP] (Elsevier B.V., 2012)
In this study, the objective was to estimate genetic parameters of body weight at 210 (BW210) and 365 (BW365) days of age in relation to rib eye area (REA), subcutaneous back fat thickness (BF) and rump fat (RF), and their respective genetic trends, in Nelore beef cattle. Estimates of genetic parameters and breeding values for the studied traits were obtained using the REML method. The direct and maternal heritability estimates were respectively: 0.25 +/- 0.02 and 0.21 +/- 0.01, for BW210, and 0.29 +/- 0.02 and 0.09 +/- 0.01, for BW365. The heritability estimates for transformed REA, BF and RF were 0.29 +/- 0.03, 0.21 +/- 0.02 and 0.23 +/- 0.03, respectively. There were genetic associations between BW210 and REA. BW365 and REA, and BF and RF, while the other correlations were low. The selection process that was conducted at the farms participating in the breeding program, taking the proposed selection index into consideration, caused genetic changes to these traits. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Beef cattle; Bos indicus; Fat thickness; Genetic correlation; Heritability; Rib eye area